Historiography of Neo-Roman Thought: Critical Review of Skinner’s Liberty before Liberalism - Reza Najafzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Quentin Skinner and a group of writers and professors of so called Cambridge School have had an undeniable role in critical rereading of history of European thought and reprinting some of the classical texts of modern political thought. Skinner, in his enormous hermeneutical studies, linking the contextualist approach to the intentionalist view, shows that the established values of today’s life style and our thinking about the values reflect a set of selections that we have made through the different historical times and possibilities. The contentious history of modern concept of liberty is such a case. Skinner puts the theory of civic liberty against the liberalism believing that the ideological triumph of liberalism in nineteenth degraded the republican cause of liberty. The republican tradition is one of the Skinner’s fields of archeological rediscovery, and surveying the trajectory of Roman political thought and analyzing historical roots of neo-Roman theory of Liberty are a part of the project of rediscovering the English republican tradition. Then, in a reductionary historicism, Skinner’s archeological hermeneutic is an English one, and his research program focused on the modern British history of liberty. His conservative archeology could not go beyond a mere historiography of thought and it is difficult to find in his project a critical position and also a philosophical examination in the field of politics. Skinner is a conservative Foucauldian.